Framework for the effective implementation of building regulations and policies – the case of Sub-Sahara African countries - Tene Nengou, Claude B. (2019)
This study of the effective implementation of government policies appraises the implementation of building policies in developing African countries, with the view of developing a framework that could increase their effectiveness. Cases of several African countries including Nigeria, South Africa, Ghana were reviewed, and then a single case study was conducted in order to effectively reach the research goal. The target country used as case study was the Republic of Cameroon. The aim of the study was attained by collecting data through a desktop review of building policies, survey questionnaires, interviews and focus group discussions with the stakeholders in Cameroon. The data was permanently triangulated using both qualitative and quantitative methods. The analysis of the collected data was guided by codes designed and developed through the usage of analytical instruments such as the Bristol Online Survey and the Nvivo10 software, as well as through the thematic analysis process. The themes were designed around various drivers of effective policy implementation theories focussing on the relationship between the overseen causes, resulting effects and observed practices in building construction procedures. The findings indicate that Building Policies are not effectively implemented. In the quest of how to address the shortcomings it transpired from the literature that although there are various instruments aiming at developing and implementing policies, there were no specific strategies with the focus on building policies or to the enhancement of the implementation level of building policies in developing countries. The lessons learned from the experiences shared and the content of various implementation theories informed the development of a strategic framework aiming at improving the implementation of existing building policies. On the basis of the data analysed, the framework for effective implementation leaning on the RIBA 2013 Plan of work was developed and assessed. A validation assessment of the potential effectiveness of the designed instrument was conducted through a focus group discussion populated by experienced representatives of most category of stakeholders of the building construction field. Feedback from the discussions and a survey gathered from participants indicate that the proposed framework which covers the entire life-cycle of a building construction is fit for its purpose and could lead to bridging the gap between the existing building policies and their effective deployment on the ground in developing countries.